Crystal structures, spectro-structural correlation and structural pathways of eight [Cu(dpyam)2(NCO)][Y] complexes (dpyam = di-2-pyridylamine), Y = Br-, CF3SO3-, BF4-· dpyam, Cl-· 4H2O, NO3-, PF6-, ClO[...]. - Sujittra Youngme (2018)
The crystal structures of eight new [Cu(dpyam)2(NCO)][Y] complexes which Y = Br-(1), CF3SO3-(2), BF4-· dpyam (3), Cl-· 4H2O (4), NO3-(5), PF6-(6), ClO4-(7) and BPh4-(8), respectively have been determined by X-ray crystallography. Five of the complexes, 1-5 (τ = 0.09-0.30) have a CuN4N′ chromophore with a trigonal bipyramidal distorted square based pyramidal (TBDSBP) stereochemistry, 6 and 7 (τ = 0.53-0.54) involve an intermediate five-coordinate stereochemistry, while 8 (τ = 0.76) involves a square base pyramidal distorted trigonal bipyramidal (SBPDTB) stereochemistry. The structures of 1-8 are compared by scatter-plot analysis with [Cu(dpyam)(NCO)][SO4]0.5· dpyam · 0.5H2O (9), the only complex of known crystal structure within this series reported to date. Scatter plots of the cations distortion isomers of the [Cu(dpyam)2(NCO)][Y] series of complexes suggests that all nine complexes lie on a common structural pathway, involving a mixture of symmetric, νsym, C2mode and asymmetric, νasym, non-C2modes of vibration of the CuN4N′ chromophore. The resulting linear and parallel structural pathways are consistent with the direct observation of the effect of vibronic coupling on the stereochemistries of the complexes, which can range from SBPDTB to TBDSBP which correlate with electronic spectral data. The EPR spectra (K-band and V-band) of complexes 1-7 are in rhombic type, while complex 8 is axial with g⊥= 2.185 and g∥= 2.005, consistent with a dz2ground state for the approximately trigonal bipyramidal stereochemistry of the CuN4N′ chromophore. These are in agreement with electronic reflectance spectra of the complexes and correspond to their stereochemistries. © 2006 Elsevier Ltd. All rights reserved.